Escola e comunidade em movimento: escola municipal Eleodoro Ébano Pereira e seus sujeitos - Gonçalves, Gisele de Souza (2022)
This thesis presents an ethnographic research, which the method is the dialectical historical materialism. The research locus is the Eleodoro Ébano Pereira Municipal School and the subjects are this places’ workers and the community that the school belongs to. To comprehend this space and it’s subjects, the theoretical referential utilized embraces especially Paulo Freire’s productions, which helps the understanding of education; ethnography authors, such as Rosana Guber; and Educação do Campo (Field Education) researchers who participated in productions about the 1998 Por Uma Educação do Campo (For A Field Education) movement, among other readings that we consider pertinent to debate, relate and contribute to the thesis. As tools for the development of the research were used: questionnaire; interviews that took place from the questionnaire; and participant observation. We present the following objectives: to know the characteristics of the school; to develop an ethnographic research with school’s subjects; identify the school's difficulties considering the contexts it went through; to present, through ethnographic research, the relations between school and community. With difficulties due to the pandemic, by virtue of social distancing and deadlines that were being reached without the possibility of having face-to-face classes, the survey – which previously had the intention to also reaching students and their families – was being adapted in order to be carried out within the new context. As the research was being developed, I realized that the school has characteristics of a rural school, but its community shows characteristics of field communities: resistance and organization to keep the school always moving. The thesis understands that the community is the subject that intensifies the school's search for its identity and strengthening. Besides that, I consider that, when arriving at the considerations, much was learned and also reviewed, not only about the subjects of the school and community, but also about the researcher as a subject of this learning process, which is valued, practiced and strengthened by this thesis’ subjects that this thesis is about, having the community as its strength and the school’s permanence in the rural region of Foz do Iguaçu as materiality, when other nearby schools ended up closing. Without the community's participation, this story could be different, but it continues and teaches a lot about resistance.